Les missions d’aide à l’orientation des enseignants-chercheurs : principes organisateurs et effets d’un engagement situé au confluent d’un ajustement de logiques - Sylvain Obajtek (Éducation et Socialisation)
This article focuses on the missions of help and guidance to the orientation of the teacher-researchers. How do they relate to these missions in a context where the orientation arrangements place the student and his / her path at the heart of the design of training systems ? How do they engage in this work space and participate in building it ? Based on a field survey carried out among a population of teacher-researchers from three universities of the Lille Academy, this research proposes to approach the representations and practices of the latter and to approach the principles organizers. This research will thus examine how teacher-researcher engagement unfolds at the center of a paradigm shift to cultivate creative tensions between social utility and professional development.